METODE PENANGGULANGAN TINDAK PIDANA CYBERBULLYING - Jamaludin, Jamaludin (UNES Law Review, 2021)
Cyberbullying is considered a serious bullying problem. The effects of cyberbullying can cause victims to feel depressed, depressed, and even commit suicide. Various methods of overcoming cyberbullying, starting from countermeasures through family, the surrounding environment to the legal system that will be used, must be enforced. This research is a normative legal research that aims to analyze methods of overcoming cyberbullying actions through penal and non-penal. The results of this study indicate that the methods of overcoming cyberbullying through penalizing efforts include: the Criminal Code, Law Number 19 of 2016 concerning Amendments to Law Number I1 of 2008 concerning Information and Electronic Transactions, and the Indonesian National Police. . While the methods of overcoming cyberbullying through non-penal efforts include: Countermeasures from KOMINFO, the community, and countermeasures from the victims themselves.